2003
DOI: 10.1007/s00115-002-1465-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuskuläre Komplikationen nach allogener Knochenmarktransplantation

Abstract: Neuromuscular syndromes following allogeneic bone marrow transplantation (BMT), although occasionally described,were not the focus of studies concerning neurologic complications following bone marrow transplantation. In this study,we summarize different polyneuropathy syndromes following BMT and report on patients with myasthenia gravis and inflammatory neuromuscular disorders such as myositis or fasciitis. Concerning the etiology of neuropathies, a neurotoxicity of immunosuppressants,a preexisting disorder du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…Few previous studies used electrodiagnostic tests to identify patients with peripheral nervous system complications. Padovan et al reported that 12 of 58 (21%) patients developed a de novo polyneuropathy after allo-HSCT and 14 (24%) distal muscular atrophy, associated with preceding severe acute GVHD, metabolic disturbances and prolonged immunosuppression [34]. In our study only two patients had a demyelinating pattern of neuropathy.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Few previous studies used electrodiagnostic tests to identify patients with peripheral nervous system complications. Padovan et al reported that 12 of 58 (21%) patients developed a de novo polyneuropathy after allo-HSCT and 14 (24%) distal muscular atrophy, associated with preceding severe acute GVHD, metabolic disturbances and prolonged immunosuppression [34]. In our study only two patients had a demyelinating pattern of neuropathy.…”
Section: Discussioncontrasting
confidence: 38%
“…Often, they manifest as GBS- or CIDP-like disease (reviewed in [6], [7]), or as mild progressive neuropathy [16], [34]. The close temporal relationship with the occurrence of GVHD and improvement upon immunosuppression in some patients suggest that neuropathies indeed are part of GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…It is often a great challenge to differentiate the muscular weakness of GVHD‐associated myositis or myopathy from that of steroid myopathy and peripheral neuropathy, particularly in patients presenting with a normal CK level and no lymphocytic infiltration in the muscle biopsy. Peripheral neuropathy and steroid myopathy are frequently induced in SCT patients by neurotoxic drugs like corticosteroids, cyclosporine, tacrolimus and thalidomide (10, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Phenotyping experiments confirmed that donor oligoclonal T cells caused this inflammatory process resembling autoimmune polymyositis (8, 9). However, a few patients with cGVHD‐related myopathy have a normal CK, lack significant lymphocytic infiltration in the muscle biopsy and rarely respond to immunosuppressive drugs (6, 10).…”
mentioning
confidence: 99%
See 1 more Smart Citation